Fantastic beasts & where to find them - Rowling, J. K. (Harry Potter, 2001)
A textbook used by apprentice wizard Harry Potter in his studies at Hogwarts School of Witchcraft and Wizardry, providing descriptions of a wide variety of magical creatures, and offering advice on their care. Proceeds from this book will go to Comic Relief U.K.